Nilai-Nilai Moderasi Beragama dalam Kebijakan Pendidikan Islam di Madrasah - Roichatul Jannah El Muttaqin; Elisa Rahmah; Haniatul Khoiroh; Muhammad Makinuddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Religious moderation is a perspective and a way of being firm in responding to and respecting religious differences, as well as differences in race, ethnicity, culture, and customs, in order to maintain unity between religious communities and be able to maintain the integrity of the Unitary State of the Republic of Indonesia. Indonesia. Therefore, the application of the values ​​of religious moderation applied in Madrasah Aliyah Negeri 2 Gresik is able to provide and apply the values ​​of religious moderation in which there is no discrimination between one another and can respect and honor one another. This study aims to determine the values ​​of religious moderation contained in Islamic education policies. This study uses qualitative research with a case study approach, whose research informants are the Deputy Head of Curriculum, teachers, and students. The results of this study indicate that MAN 2 Gresik has implemented the values ​​of religious moderation inc, including mutual respect for one another, not discriminating amidst many differences. This policy is realized through the implementation of a curriculum that integrates religious and general education, strengthening Islamic Religious Education materials, and habituating the values ​​of moderation in learning and extracurricular activities. This is in accordance with the government's Islamic education policy.   Keywords: Religious Moderation, Students, Education Policy